Standardised method for cardiomyocyte isolation and purification from individual murine neonatal, infant, and adult hearts. (September 2022) - Nicks, Amy M.; Holman, Sara R.; Chan, Andrea Y.; Tsang, Michael; Young, Paul E.; Humphreys, David T.; Naqvi, Nawazish; Husain, Ahsan; Li, Ming; Smith, Nicola J.; Iismaa, Siiri E.; Graham, Robert M.
Abstract: Primary cardiomyocytes are invaluable for understanding postnatal heart development. However, a universal method to obtain freshly purified cardiomyocytes without using different age-dependent isolation procedures and cell culture, is lacking. Here, we report the development of a standardised method that allows rapid isolation and purification of high-quality cardiomyocytes from individual neonatal through to adult C57BL/6J murine hearts. Langendorff retrograde perfusion, which is currently limited to adult hearts, was adapted for use in neonatal and infant hearts by developing an easier in situ aortic cannulation technique. Tissue digestion conditions were optimised to achieve efficient digestion of hearts of all ages in a comparable timeframe (<14 min). This resulted in a high yield (1.56–2.2 × 10 6 cells/heart) and viability ( 70–100%) of cardiomyocytes post-isolation. An immunomagnetic cell separation step was then applied to yield highly purified cardiomyocytes ( 95%) as confirmed by immunocytochemistry, flow cytometry, and qRT-PCR. For cell type-specific studies, cardiomyocyte DNA, RNA, and protein could be extracted in sufficient yields to conduct molecular experiments. We generated transcriptomic datasets for neonatal cardiomyocytes from individual hearts, for the first time, which revealed nine sex-specific genes (FDR < 0.05) encoded on the sex chromosomes. Finally, we also developed an in situ fixation protocol that preserved the native cytoarchitecture of cardiomyocytes ( 94% rod-shaped post-isolation), and used it to evaluate cell morphology during cardiomyocyte maturation, as well as capture spindle-shaped neonatal cells undergoing cytokinesis. Together, these procedures allow molecular and morphological profiling of high-quality cardiomyocytes from individual hearts of any postnatal age. Graphical abstract: Unlabelled Image Highlights: Standardised cell isolation and purification from neonatal through to adult hearts. High-quality cardiomyocytes isolated by Langendorff perfusion of individual hearts. Rapid purification for cardiomyocyte-specific studies of DNA, RNA, and protein. Sex-specific genes identified in the neonatal cardiomyocyte transcriptome. In situ fixation protocol preserves cardiomyocyte cytoarchitecture post-isolation.